Walk 'til You Run Out of Water - Phillips, Perdita (Routledge Journals, Taylor & Francis Ltd, 2012)
This image essay brings together notions of dehydration and lostness in outback walking (based on personal experience) with its ecological counterpoint of the rapid change occurring in our world today. Analogical comparisons are drawn between the point where walking loses its rhythm (because of exhaustion) with ecosystems that, too, appear to have lost their way. Questioning whether it is only through rhythmic walking that positive states can occur, it is proposed that walking out-of-step leads to contrapuntal adjustments that can reinvigorate creative practice, utilising the same ‘adjustment to failure’ strategies critical to the experimental nature of contemporary art practice. The continual fine-tuning required for traversing rough ground also reflects the dynamic nature of ecosystems, which are permanently adjusting to change. Recent ecological theory's focus on complex adaptive systems – and resilience rather than stability – means that our responses to ecosystems and the pressures we are placing upon them, must be dynamic, responsive and contingent. Does the sharpness of being without water focus us on the shifting socio-ecological conditions ahead? Walking and bodily sensitisation to place opens us up to different spatial and temporal scales. In making linkages with disability philosophy and research into community inaction in the face of climate change, it is argued that the inflection or break-in-step of a resilient style of walking can also be employed for creative socio-ecological change.